Anomalous hydrogen production during photolysis of nahco3 mixed water - Shahid, Muhammad; Bidin, Noriah; Mat Daud, Yacoob; Talha, Muhammad; Ullah, M.Inayat (Research Publication IJSER, 2011)
Production and enhancement of hydrogen on large scale is a goal towards the revolution of green and cheap energy. Utilization of hydrogen energy has many attractive features, including energy renewability, flexibility, and zero green house gas emissions. In this current research the production and the enhancement of hydrogen from the NaHCO3 mixed water have been investigated under the action of diode pumped solid state laser with second harmonic of wavelength 532nm. The efficiency of the hydrogen and oxygen yields was found to be greater than the normal Faradic efficiency. The parametric dependence of the yields as a function of laser irradiation time, Laser focusing effect and other parameters of the electrolysis fundamentals were carefully studied.